2007
DOI: 10.1128/aem.02042-06
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bacterial Groups Preferentially Associated with Mycorrhizal Roots of Medicago truncatula

Abstract: Mycorrhizae result from symbiotic associations between soil fungi and the roots of most plants. Mycorrhizae are considered to be classic examples of mutualistic symbioses. The basis for this mutualism relies on the supply of carbon to the fungus by the host plant and, in return, on the supply of mineral nutrients and water to the plant and on the plant's protection against soil-borne diseases by the fungus (41). Among mycorrhizal symbioses, arbuscular mycorrhizae (AM) are the most widespread. AM are recorded i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
68
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 42 publications
6
68
0
Order By: Relevance
“…Increasingly now, a number of reports have mentioned the possible interactions of this group of bacteria with (mycorrhizal) fungi. Oxalobacteraceae have been found to preferentially associate with mycorrhizal roots rather than with the roots of plant mutants that cannot form the AMF symbiosis (Offre et al, 2007(Offre et al, , 2008. The similarity between the findings of these experiments, which were performed in natural soil, and our results that were obtained from a more controlled, but artificial system is a strong indication that we are looking at realistic interactions.…”
Section: Discussionsupporting
confidence: 50%
“…Increasingly now, a number of reports have mentioned the possible interactions of this group of bacteria with (mycorrhizal) fungi. Oxalobacteraceae have been found to preferentially associate with mycorrhizal roots rather than with the roots of plant mutants that cannot form the AMF symbiosis (Offre et al, 2007(Offre et al, , 2008. The similarity between the findings of these experiments, which were performed in natural soil, and our results that were obtained from a more controlled, but artificial system is a strong indication that we are looking at realistic interactions.…”
Section: Discussionsupporting
confidence: 50%
“…Recently, it was shown that the wild-type and symbiosisdefective mutants of the model legume Medicago truncatula possess different bacterial community structures and that certain bacteria preferentially associate with mycorrhized roots (29). This example indicates that genetic alteration in the nodulation/mycorrhization signaling pathways can in turn alter the accompanying plant microflora, aside from rhizobia and mycorrhizae.…”
mentioning
confidence: 99%
“…Although plants are known to control the degrees of nodulation and mycorrhization of roots by rhizobia and mycorrhizae, respectively, through autoregulation systems (Carroll et al, 1985;Meixner et al, 2007), the effects of the autoregulation systems on the other plant-associated microorganisms in the phytosphere remain unclear (Parniske, 2000). Recent studies have shown that the wild-type and symbiosisdefective mutants of legumes such as Medicago truncatula and Glycine max have different microbial community structures, and certain microbes associate preferentially with nodulated or mycorrhizal root systems (Offre et al, 2007;Ikeda et al, 2008a). Furthermore, transcriptional analyses revealed that both nodulation and mycorrhization systemically induced a series of defense genes in a host plant and consequently increased its disease resistance (Liu et al, 2007;Kinkema and Gresshoff, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, a method was recently developed for enriching the bacterial cells collected from soybean stems . The enrichment method allows the construction of a clone library of the bacterial 16S ribosomal RNA (rRNA) genes, which provides better resolution for examining the microbial community structures compared with the limited analyses in previous studies based mainly on fingerprinting methods (Offre et al, 2007;Ikeda et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%